Barriers and potential challenges in the development of social businesses in the Czech Republic - Wildmannová, Mirka (Univerzita Pardubice, 2017)
Social entrepreneurship is characterised by a high degree of innovation and creativity. The topic of social entrepreneurship is currently often discussed and it is one of the trends of contemporary social economy in the CR. The Czech Republic is one of the countries that start discovering the benefits of social business, especially at the regional level. Experience from abroad clearly identifies the positive impacts of social entrepreneurship on the national economy. Social enterprises are one of the major stakeholders in the labour market employing socially disadvantaged people. This paper aims to identify the main barriers to the activities of social enterprises. To identify those barriers, use was made of a questionnaire survey in social businesses. Based on the results of the survey it was identified that the current main barriers include the non-existence of the social entrepreneurship act, insufficient definition of criteria for social enterprises and inadequate inter-departmental coordination. Potential future challenges appear to be legislative and systematic state financial support and preparation of the environment for social activities within the framework of regional cooperation including the establishment of social incubators.
Keywords: social economy; social policy; public administration; social enterprise; social cooperatives; L31; M14